FAKTOR-FAKTOR KEGAGALAN UNAMIR (UNITED NATIONS ASSISTANCE MISSION FOR RWANDA) DALAM MISI PERDAMAIAN KONFLIK ETNIS DI RWANDA 1993 – 1996 THE FAILURE FACTORS TOWARD UNAMIR PEACE MISSION OF ETHNIC CONF - Andina Alisya Amanda (HI 16 UMY 072, 2016)
*72 This research aims to explain the factors that led to the failure factors toward UNAMIR (United Nations Assistance Mission for Rwanda) peace mission of ethnic conflict in Rwanda in 1993-1996. Technique of data collection method is secondary data. Secondary data use literature material such as books, journals, and articles. Researcher also support data by downloading data on several site from internet which relevant with aim of the research. This research discuss analytical description about the failure of UNAMIR in resolving ethnic conflicts and prevent genocide in Rwanda. UNAMIR was a peacekeeping operation established by the UN to help countries resolve the conflict Rwanda. But the troops have failed in peace efforts between the ethnic conflict between Hutu and Tutsi are. Conflict continued until the genocide, but again UNAMIR was unable to stop the genocide.